2023
DOI: 10.30442/ahr.0901-05-189
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Prostate Specific Antigen (PSA) Point-of-Care-Testing (POCT) Techniques

Abstract: Background: Prostate Specific Antigen (PSA) testing is widely used to diagnose and monitor clinical progress in patients with prostate cancer. The availability of various new Point-of-Care-Testing (POCT) equipment for PSA demands that the performance characteristics of these equipment be assessed before introducing them into clinical use to ensure accuracy and reliability. Objectives: To compare the i-CHROMA® automated immunofluorescence serum total PSA assay with the Accubind® Enzyme Linked Immuno-Sorbent Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…A similar study done at OAUTH by Ajala and his colleagues showed a good correlation between the i-CHROMA™ and the Accubind ® Enzyme Linked Immuno-Sorbent Assay (ELISA) (r = 0.956) [9]. A previous study done by our team showed that the Abbott Architect PSA laboratory method and the i-CHROMA™ PSA method had a good correlation (r 2 = 0.90845) using venous and finger-prick samples [10].…”
Section: Discussionmentioning
confidence: 68%
“…A similar study done at OAUTH by Ajala and his colleagues showed a good correlation between the i-CHROMA™ and the Accubind ® Enzyme Linked Immuno-Sorbent Assay (ELISA) (r = 0.956) [9]. A previous study done by our team showed that the Abbott Architect PSA laboratory method and the i-CHROMA™ PSA method had a good correlation (r 2 = 0.90845) using venous and finger-prick samples [10].…”
Section: Discussionmentioning
confidence: 68%